Advances in RNA-based therapeutics: current breakthroughs, clinical translation, and future perspectives - Makkar, Sarbjeet Kaur (Frontiers in Genetics, 2025)
RNA-based therapeutics have revolutionized modern medicine, offering versatile and precise modalities to modulate gene expression for a wide range of diseases including infectious diseases, genetic disorders, and cancer. This review comprehensively examines the evolution and current landscape of RNA therapeutics, encompassing major classes such as mRNA vaccines, small interfering RNAs (siRNAs), antisense oligonucleotides (ASOs), and emerging RNA editing technologies like CRISPR-Cas13. We discuss technological innovations that have overcome historic challenges related to RNA instability, immunogenicity, and delivery, with particular emphasis on lipid nanoparticle formulations and targeted ligand conjugates. Clinical translation milestones, regulatory considerations, and safety profiles are analyzed, highlighting recent approvals and ongoing trials that underscore the therapeutic promise of RNA modalities. Despite these advances, critical challenges including off-target effects, immune activation, manufacturing scalability, and effective delivery to extrahepatic tissues remain to be addressed. The integration of personalized RNA therapeutics, precision RNA editing, and artificial intelligence-driven design and clinical decision support heralds a new era of individualized and adaptive therapies. This synthesis of molecular biology, nanotechnology, and computational innovation not only illustrates the transformative potential of RNA therapeutics but also charts a path toward broad clinical impact and accessible precision medicine. To fully realize this potential, the field must prioritize the development of robust regulatory frameworks and adaptive clinical trial designs to ensure equitable access, while also advancing exploration of emerging modalities such as circular RNAs, self-amplifying RNAs, and RNA-targeting small molecules. Collectively, these innovations are poised to expand the therapeutic landscape beyond current boundaries and accelerate the realization of truly personalized RNA medicine. Looking ahead, progress in RNA therapeutics will depend less on the expansion of new classes alone and more on solving practical challenges in tissue targeting, long-term safety, scalable production, and regulatory adaptation. By comparing established and emerging approaches through these dimensions, this review provides a forward-looking synthesis that identifies where translation is already feasible and where innovation is still required.